Intraspecific Evaluation of Phenotypic Variations of Caryopteris incana (Thunb. ex Houtt.) Miq. in Western Kyushu, Japan - Masaya Ando; Takanori Kuronuma; Hitoshi Watanabe (Plants, 2025)
Caryopteris incana (Thunb. ex Houtt.) Miq., an endangered species native to western Kyushu, Japan, forms locally isolated populations. In our previous studies, we conducted a distribution survey of 109 populations across four regions and performed phylogenetic analyses using chloroplast DNA to clarify their genetic structure and diversity. The primary objective of this study was to clearly compare and evaluate phenotypic differences that are considered to be genetically fixed among adaptive traits evolved in response to the native environments of each region. We evaluated morphological characteristics—such as floral parts, leaves, and plant form—under uniform cultivation conditions using seeds collected from native populations. As a result, region-specific phenotypes were identified, and diverse variations were observed both among and within regions. Furthermore, the presence of phenotypes with high coefficients of variation even within the same region suggests the existence of diverse gene pools suitable for various applications. This study not only contributes to understanding the regional adaptive strategies of C. incana, but also provides fundamental data for developing conservation plans for this endangered species. Additionally, the phenotypic information obtained is expected to be useful for breeding horticultural varieties and for setting future conservation priorities.